Common mental health and emotional and behavioural disorders among adolescents and young adults in Harare and Mashonaland East, Zimbabwe: a population-based prevalence study. Issue 3 (14th March 2023) - Doyle, Aoife Margaret; Bandason, T; Dauya, E; McHugh, Grace; Grundy, Chris; Simms, Victoria; Chibanda, D; Ferrand, Rashida
Abstract : Objectives: To estimate the prevalence of common mental health disorders (CMDs) and emotional and behavioural disorders among young people and to explore the correlates of CMDs risk. Setting: Five urban and periurban communities in Harare and Mashonaland East, Zimbabwe Design: Population-based cross-sectional study Participants: Young people aged 13–24 years living in households in the study areas. Outcome measures: The primary outcome was the proportion of participants screening positive for probable CMDs defined as a Shona Symptoms Questionnaire (SSQ) score ≥8. Secondary outcomes were emotional and behavioural disorders measured using the Strength and Difficulties Questionnaire (SDQ), and adjusted ORs for factors associated with CMD. Results: Out of 634 young people, 37.4% (95% CI 33.0% to 42.0%) screened positive for probable CMDs, 9.8% (95% CI 7.5% to 12.7%) reported perceptual symptoms and 11.2% (95% CI 9.0% to 13.8%) reported suicidal ideation. Using UK norms to define normal, borderline and abnormal scores for each of the SDQ domains, a high proportion (15.8%) of Zimbabwean young people had abnormal scores for emotional symptoms and a low proportion had abnormal scores for hyperactivity/inattention scores (2.8%) and prosocial scores (7.1%). We created local cut-offs for the emotional symptoms, hyperactivity/attention and prosocial SDQ domains. The odds of probable CMDs increased with each year of age (OR 1.09, p<0.001) and was higher among those who were out of school and not working compared with those in school or working (adj. OR 1.67 (1.07, 2.62), p=0.04). One in five participants (22.1%) were referred immediately for further clinical assessment but uptake of referral services was low. Conclusions: We observed a high prevalence of symptoms of CMDs among general population urban and peri-urban young people especially among those with no employment. There is a need for more accessible and acceptable youth-friendly mental health services.